The Inflation Surge of 2021–22: Scarcity of Goods and Commodities, Strong Labor Markets and Anchored Inflation Expectations - Ángel Ubide (Intereconomics)
Abstract The key to understanding the series of supply shocks that have hit inflation is the nature of the COVID-19 recession.